Effect of Justicia insularis Leaf Extract and Fractions on Oxidative Stress Markers, Liver Function Parameters and Liver Histology of Plasmodium berghei -Infected Mice - Enyiekere, Veronica James; Anagboso, Martin Osita; Ise, Uduak Peter; Essien, Grace Emmanuel; Okokon, Jude Efiom; Ebong, Nwakaego Omonigho (Biology, Medicine, & Natural Product Chemistry, 2024)
Justicia insularis (Family-Acanthaceae) is used in Ibibio ethnomedicine to treat malaria. The leaf extract and fractions of J. insularis were investigated for antioxidative stress and hepatoprotective activities in Plasmodium berghei-infected mice. The leaf extract (100-300 mg/kg, p.o.) exerted significant (p<0.05) antimalarial activity against P. berghei infection in curative test with ethyl acetate fraction demonstrating the highest activity.  The extract/fractions treatment caused significant (p<0.05) reductions in liver enzymes (ALT, AST and ALP), total and conjugated bilirubin of the treated infected mice and also decreased significantly (p<0.05) total protein and albumin levels of the treated mice relative to control. The leaf extract and fractions further improved significantly (p<0.05) the levels of oxidative stress markers enzymes and molecules (CAT, GPx, GST, SOD) of the treated infected mice with no significant (p>0.05) effect on GSH. The MDA levels in the livers of the treated infected mice were significantly (p<0.05) reduced relative to control. Histology of liver sections revealed absence or significant reductions in pathological features in infected mice treated with leaf extract (100 mg/kg), DCM and ethyl acetate fractions compared to untreated infected mice. These results suggest that the leaf extract/fractions of Justicia insularis possess antioxidative stress and hepatoprotective potentials, which is an added advantage to its antimalarial property.